Analytical performance evaluation elektroochistiteley with a fibrous filler dielectric - Гаража, В.В.; Хынг, Динь Тан (Proceedings of National Aviation University (archive), 2007)
The falling out process of particles of the contamination is сonsidered on surfaces of the filaments polarized stuff under the action of external electric field. The falling out surface is prototyped in the manner of matrix structure. The equation to efficiency of the work polarized electrocleaner (EO) is received on the grounds of analysis of the moving the single particle under the action of external power on surface of the filaments of the stuff. Broughted check to adequacy of the equation to efficiency at variation controlling parameters of the process electrocleaning: the lengths, density of the packing the filaments of the stuff, voltages on electrode and time of the processing dispersion in electric field.